2015
DOI: 10.1016/j.jad.2014.12.036
|View full text |Cite
|
Sign up to set email alerts
|

The roles of resilience and childhood trauma history: Main and moderating effects on postpartum maternal mental health and functioning

Abstract: Objective Recently postpartum women participated to investigate main and moderating influences of resilience and childhood history of maltreatment on posttraumatic stress disorder (PTSD), major depressive disorder (MDD), parental sense of mastery, and family functioning. Method At 4-months postpartum, 214 mothers (145 with a history of childhood abuse or neglect) completed interviews assessing mental health symptoms, positive functioning, resilience and trauma history. Multiple and moderated linear regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
81
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 45 publications
9
81
2
Order By: Relevance
“…Specifically, a study examining two populations found lower resilience, as assessed by the Connor-Davidson Resilience Scale (CD-RISC; Connor and Davidson, 2003), predicting suicide attempts in those with CM histories (Roy et al, 2011). A recent investigation by Sexton et al (2015) in postpartum women showed that resilience, CM severity, and their interaction were associated with PTSD and MDD postpartum. Given the associations between CM, shame, resilience and psychiatric functioning, continued efforts to understand relationships between these factors and postpartum SI are warranted.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, a study examining two populations found lower resilience, as assessed by the Connor-Davidson Resilience Scale (CD-RISC; Connor and Davidson, 2003), predicting suicide attempts in those with CM histories (Roy et al, 2011). A recent investigation by Sexton et al (2015) in postpartum women showed that resilience, CM severity, and their interaction were associated with PTSD and MDD postpartum. Given the associations between CM, shame, resilience and psychiatric functioning, continued efforts to understand relationships between these factors and postpartum SI are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…During the postpartum period, women reflect on their own childhoods, thus triggering prior memories and experiences that result in emotional (psychopathology) as well as behavioral (parenting) disruptions (Lyons-Ruth & Block, 1996; Wright, Fopma-Loy, & Oberle, 2012). The frequency and severity of CM are known to predict increased psychopathology in adult postpartum populations (Choi and Sikkema, 2015; Grekin and O’Hara, 2014; Leigh and Milgrom, 2008; Muzik et al, 2013; Sexton et al, 2015). Sit et al’s (2015) investigation established a relationship between CM and SI in mothers with postpartum depressive disorder (PPD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is extensive literature supporting a link between childhood maltreatment (CM) exposure and adverse mental health outcomes in adulthood. In particular, major depressive disorder (MDD), Posttraumatic Stress Disorder, anxiety, interpersonal aggression, and suicide attempts are frequently noted sequelae in adults reporting abuse and neglect in early development (Hamilton, Micol-Foster, & Muzik 2015; Harford & Grant 2014; Kaplow & Widom 2007; Sexton, Hamilton, McGinnis, Rosenblum, & Muzik 2015). Compounding these threats to public health, a history of CM increases risk of recurrent depressive episodes throughout the lifespan and is associated with more treatment refractory responses to evidence based interventions for postpartum depressive symptoms (PDS) (Cort et al 2012; Nanni, Uher, & Danese 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review confirmed robust relationships between CM and perinatal mood disorders (Choi & Sikkema 2015; Buist & Janson, 2001). Further, studies have identified associations between CM, maternal psychopathology, and mother-infant bonding and child development, thus increasing the probability of intergenerational transmission of risk (e.g., Martinez-Torteya et al 2014; Muzik et al 2013; Sexton et al 2015). …”
Section: Introductionmentioning
confidence: 99%